PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PENELITIAN PADA UPT. PPKM ( UNIT PELAKSANA TUGAS PENELITIAN PENGABDIAN KEPADA MASYARAKAT ) POLITEKNIK NEGERI PADANG - Deni Satria; Defni defni; Ervan Asri; Indri Rahmayuni (Elektron : Jurnal Ilmiah, 2013)
This study aimed to create an information system on UPT.PPKM Padang State Polytechnic where the system is initially UPT.PPKM are still using Microsoft Access to process data that existing research. So that would make it difficult for employees to process the data, find the data if necessary and to report the research itself. The results of this study are expected to generate a summary report every major research, courses, lecturers so as to facilitate the search data related to research quickly. Making this system using PHP and MySQL